Building a Globally Oriented Organizational Culture: The Role of HR Management in Facing Competition in the International Era - Sumiati Sumiati (PT. Hafasy Dwi Nawasena, 2025)
Globalization has had significant implications for the dynamics of competition between organizations, demanding an adaptive and globally oriented organizational culture. In this context, human resource management (HRM) has a strategic role to ensure that organizations are able to manage diversity, improve cross-cultural competencies, and create a work climate that supports innovation and international collaboration. This study aims to analyze the contribution of HRM in building a global organizational culture as a strategy to face competition in the era of globalization. The research method used is a literature review with a descriptive qualitative approach, which examines various scientific literature, indexed articles, and relevant academic publications over the last ten years. The analysis was conducted using qualitative content analysis techniques by identifying key themes related to global recruitment strategies, cross-cultural competency development, workforce diversity management, and the role of leadership in strengthening organizational culture. The results of the study show that HR management plays a crucial role in encouraging organizations to become more adaptive, innovative, and globally competitive through the implementation of talent management strategies based on international competencies. The development of a global organizational culture has been proven to enhance long-term competitive advantage by creating synergy between local values and universally recognized global standards. In conclusion, an organization's success in facing global competition is largely determined by the ability of its human resource management to build and internalize an organizational culture that is responsive to the dynamics of globalization